UPLC-ESI-QTOF-MS/MS Analysis of the Phytochemical Compositions From Chaenomeles speciosa (Sweet) Nakai Fruits. (4th February 2022) - Tao, Weili; Zhao, Chuanyi; Lin, Gengxue; Wang, Qiongjin; Lv, Qian; Wang, Shuyun; Chen, Yicun
Abstract: Chaenomeles speciosa (Sweet) Nakai (C. speciosa Nakai) is a popular fruit widely used in China for its health-promoting properties. The presences of phytochemical compositions in the plants play an important role in the health benefits. Nevertheless, the detailed information of these ingredients is still unknown. Therefore, in this work, an untargeted analytical method based on ultra-high-performance liquid chromatography-quadrupole-time of flight coupled to mass spectrometry in two different ionization modes was used to qualitative the phytochemicals in C. speciosa Nakai, meanwhile, the anti-inflammatory activity of these phytochemicals was researched through detecting the inhibition of nitric oxide (NO) that was induced by lipopolysaccharide in RAW 264.7 murine macrophage cells. The results showed that there were totally 175 primary and secondary metabolites were identified in the fruit of C. speciosa Nakai, including phenols, terpenoids, flavonoids and other phyto-constituents. Actually, most compounds were described in C. speciosa Nakai fruits for the first time. Besides, the anti-inflammatory activity was measured by the result of NO inhibition rate, the consequence showed that the value of half-inhibitory concentration (IC50 ) was 365.208 μg/mL. These results indicate that C. speciosa Nakai is an efficient medicinal fruit, which owns various bioactivities and has the potential to treat various diseases.